University campus in heritage cities: contrasts between Cáceres and Toledo - Campesino Fernández, Antonio José; Salcedo Hernández, José Carlos (CIAN-Revista de Historia de las Universidades, 2014)
From its medieval origin, the urban nature of the university function, found its perfect ecosystem in genetic cores of privileged historic European cities, became “campus”. In this traditional pattern of centralized university, college life and city life were joined in perfect cultural symbiosis for centuries, leaving their mark on the urban morphologies and structures. The traditional university pattern went into crisis in the first decades of the twentieth, under zoning functionalist theory, with the emergence of “campus” that broke the historical balance University-City. The new “college town” is now understood as a peripheral niche of physical, social, functional and environmental segregation, strangling the only integrator link between University and Society. In Spain, during the last four decades, university shapes and functions have remained dualities of behaviors, choosing some of them by location Historic Centers, through rehabilitation and re-functioning of heritage architecture, while others chose peripheral locations on architectures newly minted on American campus. We try to review these college second generation patterns, contrasting lights and shadows. We will do it with the comparative study between Cáceres and Toledo.
Keywords: Campus; heritage; rehabilitation; revitalization; architectures